Reforming the labor market and improving competitiveness: An analysis for Spain using FiMod - Tim Schwarzmüller; Nikolai Stähler (SERIEs - Journal of the Spanish Economic Association, 2013)
This paper uses an extended version of 'FiMod-A DSGE Model for Fiscal Policy Simulations' (Stähler and Thomas Econ Model 29:239-261, 2012) with endogenous job destruction decisions by private firms to analyze the effects of several currently discussed labor market reforms on the Spanish economy. The main focus is on the firms' hiring and firing decisions, on the implications for fiscal balances and on Spain's international competitiveness. We find that measures aiming at reducing (policy-induced) outside option of workers, such as a decrease in unemployment benefits, public wages or, to a lesser extent, public-sector employment, seem most beneficial to foster output, employment, international competitiveness and fiscal balances. Decreasing the unions' bargaining power also accomplishes this task. Our simulation suggests that reforming employment protection legislation does not seem to be a suitable tool from the perspective of improving international competitiveness. All measures imply (income) redistribution between optimizing and liquidity-constrained consumers. Our analysis also suggests that those reforms that are beneficial for Spain generate positive spillovers to the rest of EMU, too.
Keywords: E24; E32; E62; H20; H50; 330; General equilibrium; Fiscal policy simulations; Labor market reforms